Reinterpreting Ḍarb In Islamic Family Law: A Maqāṣid-Based Socio-Legal Approach - Muhammad Amar Adly; Ardiansyah Ardiansyah; Hasan Matsum; Fikfik Taufik; Najib A. Gisymar (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
Domestic violence in Muslim family contexts is sometimes reinforced by literalist interpretations of QS. An-Nisāʾ: 34, especially the term ḍarb, which has often been read as permitting physical discipline within marriage. This study aims to reconstruct the meaning of ḍarb in Islamic family law in order to prevent its use as a religious justification for domestic violence. Using a qualitative normative method with a socio-legal orientation, the study examines classical tafsīr, the views of the four Sunni legal schools, Prophetic traditions, and Indonesian legal instruments on domestic violence. The analysis combines uṣūl al-fiqh, maqāṣid-based reasoning, and contextual interpretation to assess whether classical legal meanings remain valid when they produce harm in contemporary family life. The findings show that classical Islamic legal sources did not treat ḍarb as an unrestricted right of husbands. Instead, they placed it under strict limitations, including procedural sequence, non-injury, ethical restraint, and legal accountability. The Prophetic model further shifts the norm toward non-violence, compassion, and protection of dignity. Based on these findings, this study argues that ḍarb should be reconstructed not as physical punishment, but as a restricted and non-violent mechanism of conflict resolution oriented toward reconciliation and harm prevention. The study contributes to Islamic family law reform by offering an uṣūlī–socio-legal framework that can guide religious judges, mediators, family-law institutions, and anti-domestic violence policy in preventing the misuse of religious texts to legitimize violence.